(untitled) (The Peerian Journal, 2023)
This This work aims at an applied study of the process of adding different percentages of aluminum oxide to aluminum alloys that are widely used and the effect of these additives on a major set of physical properties, and the results obtained showed an increase in the strength and quality of samples reinforced with nano-materials compared to the base material